2018
DOI: 10.1051/e3sconf/20183705002
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of gravity data and Sentinel-1 image for structural mapping. Case of Beni Mellal Atlas and Beni Moussa plain (Morocco).

Abstract: Abstract. The present work is a combined study of gravity and Sentine-1 data for fracture mapping in the karstic massif of Beni Mellal Atlas and the adjacent plain of Beni Moussa. In order to locate the various faults that contribute to the study area structuring, the gravimetric contacts analysis method, based on the joint use of the horizontal gradient and the upward continuation at different altitudes, has been applied to the gravity data. To optimize the structural mapping in the study area, the gravimetri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The areas with high anomalies (P2, P3 and P4) are attributed to basaltic flows intercalated between Figure 9-Extracted lineaments from processing Sentinel-1 image (Boutirame et al, 2018). the mid-Jurassic "red beds" (Souhel 1996;Michard et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The areas with high anomalies (P2, P3 and P4) are attributed to basaltic flows intercalated between Figure 9-Extracted lineaments from processing Sentinel-1 image (Boutirame et al, 2018). the mid-Jurassic "red beds" (Souhel 1996;Michard et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In the western part of the study area, four geomorphological and structural zones have been identified; thoses zones correspond to two depressions and two high regions separated by major structural accidents (Figure 10). We distinguish from north to south: Beni Moussa plain (N1), the border zone of Afourer Atlas (P1, P2 and P3), Ait Attab syncline zone (N2) and the Ait Rhouja (Boutirame et al, 2018). the mid-Jurassic "red beds" (Souhel 1996;Michard et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The map of the residual magnetic field revels positive and negative anomalies of different shapes and amplitudes which testify to the variation of the magnetization in the subsoil [13]. In order to better visualize these magnetic anomalies and facilitate the analysis and structural interpretation of the results of the treatments were performed using filters and operators based on the mathematical software.…”
Section: Separation Of the Residual And The Regionalmentioning
confidence: 99%
“…This reduction makes it possible to eliminate the distortion of the anomalies caused by the inclination of the Earth's magnetic field by transforming the magnetic anomaly as if it were located at the North Magnetic Pole and to put the anomalies back on top of the sources which create them, to condition that the magnetization is not persistent. [13,17,19] In order to achieve this reduction we calculated the inclination and the declination of the study area, their values are respectively 43.5° N and -0.7° W. The usefulness of this transformation operator resides in the fact that it enhances all the magnetic anomalies to be low or high amplitudes, indeed another advantage of the transformation is that by calculating an angle, all the forms will be represented in ways similar, whether the anomalies are of low oh high amplitude. The operator is applied to the map of the magnetic anomaly reduced to the pole; for a vertical contact, the null value of the angle corresponds to the limit of the structure.…”
Section: Separation Of the Residual And The Regionalmentioning
confidence: 99%